Intimate Accounts of Education Policy Research : The Practice of Methods - Addey, Camilla; Piattoeva, Nelli (Abingdon, Oxon ; New York, NY : Routledge, 2022)
What do we actually do when we research education policy and governance? Why do we tame the messy hinterland of research into smooth accounts and what do we lose in the process? In this volume, distinguished scholars in education policy and governance research discuss how the practice of methods is messy, subjective, and provisional. They approach methodology as riddled with tensions, doubts, troubles, and mundane decisions. Scholarship in this book shifts from recording the methodological hinterland to putting it to productive use as resources for thinking about the researched world and about research itself. This methodological openness helps to examine how research reproduces scholars' metaphysics, how research is a deeply embodied process encompassing all senses, how scholars' concerns interfere in the worlds they study, but also how these equally interfere with researchers. By challenging smooth methodological accounts which conceal the complex and provisional nature of research, this book offers new approaches in education policy and governance research that are more generative, insightful, and sincere. Offering new ways of thinking about research methodologies, the book will be of great interest to researchers, academics, and post-graduate students in the fields of education research and education theory, as well as social scientists interested in research methodologies more broadly.
Keywords: Education and state -- Research; EDUCATION / Educational Policy & Reform / General; EDUCATION / Research